2018
DOI: 10.22175/mmb2017.07.0039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multiple Antimicrobial Interventions on Ground Beef Quality

Abstract: Multiple antimicrobial intervention strategies are employed in beef manufacturing, and some may impact quality and palatability of ground beef patties. Combinations of antimicrobial treatments -hot water (at least 82 °C), lactic acid (4.0 to 5.0%), acidified sodium chlorite (pH of 2.7 to 2.8) and Beefxide (lactic/citric acid mixture; up to 2.5%) -were applied to hot or chilled carcasses and trimmings before manufacturing ground beef patties, which were designated for color evaluation, consumer panel, or traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Similarly, in the present study, no differences were found in other flavor attributes (e.g., beef flavor identity, browned, roasted), which result from a combination of odor and taste (Legako et al, 2015). Eastwood et al (2018) also reported that multiple interventions (control, acidified sodium chloride, Beefxide, and LA) applied prechilling or postchilling on carcasses and on beef trimmings have minimum effect on ground beef flavor.…”
Section: Trained Sensory Analysissupporting
confidence: 65%
“…Similarly, in the present study, no differences were found in other flavor attributes (e.g., beef flavor identity, browned, roasted), which result from a combination of odor and taste (Legako et al, 2015). Eastwood et al (2018) also reported that multiple interventions (control, acidified sodium chloride, Beefxide, and LA) applied prechilling or postchilling on carcasses and on beef trimmings have minimum effect on ground beef flavor.…”
Section: Trained Sensory Analysissupporting
confidence: 65%